Does regular post-exercise cold application attenuate trained muscle adaptation? - Yamane, M.; Ohnishi, N.; Matsumoto, T. (International Journal of Sports Medicine, 2015)
This study examined the effects of regular post-exercise cold application on muscular and vascular adaptations induced by moderate-intensity resistance training. 14 male subjects participated in resistance training: 5 sets of 8 wrist-flexion exercises at workload of 70-80% of the single repetition maximum, 3 times a week for 6 weeks. 7 subjects immersed their experimental forearms in cold water (10±1°C) for 20?min after wrist-flexion exercises (cooled group), and the other 7 served as control subjects (noncooled group). Measurements were taken before and after the training period; wrist-flexor thickness, brachial-artery diameter, maximal muscle strength, and local muscle endurance were measured in upper extremities. Wrist-flexor thicknesses of the experimental arms increased after training in both groups, but the extent of each increase was significantly less in the cooled group compared with the noncooled group. Maximal muscle strength and brachial-artery diameter did not increase in the cooled group, while they increased in the noncooled group. Local muscle endurance increased in both groups, but the increase in the cooled group tended to be lower compared to the noncooled group. Regular post-exercise cold application to muscles might attenuate muscular and vascular adaptations to resistance training.